ChemInform Abstract: Catalytic Amidation of Unactivated Ester Derivatives Mediated by Trifluoroethanol. Issue 41 (October 2015) - Caldwell, Nicola; Jamieson, Craig; Simpson, Iain; Watson, Allan J. B.
Abstract A novel and versatile organocatalytic amidation method facilitated by inexpensive 2, 2, 2‐trifluoroethanol is presented.